Exploring the Franck–Condon region of a photoexcited charge transfer complex in solution to interpret femtosecond stimulated Raman spectroscopy: excited state electronic structure methods to unveil non-radiative pathways. Issue 23 (11th May 2021) - Coppola, Federico; Cimino, Paola; Raucci, Umberto; Chiariello, Maria Gabriella; Petrone, Alessio; Rega, Nadia
Abstract : We present electronic structure methods to unveil the non-radiative pathways of photoinduced charge transfer (CT) reactions that play a main role in photophysics and light harvesting technologies. Abstract : We present electronic structure methods to unveil the non-radiative pathways of photoinduced charge transfer (CT) reactions that play a main role in photophysics and light harvesting technologies. A prototypical π-stacked molecular complex consisting of an electron donor (1-chloronaphthalene, 1ClN) and an electron acceptor (tetracyanoethylene, TCNE) was investigated in dichloromethane solution for this purpose. The characterization of TCNE:π:1ClN in both its equilibrium ground and photoinduced low-lying CT electronic states was performed by using a reliable and accurate theoretical–computational methodology exploiting ab initio molecular dynamics simulations. The structural and vibrational time evolution of key vibrational modes is found to be in excellent agreement with femtosecond stimulated Raman spectroscopy experiments [R. A. Mathies et al., J. Phys. Chem. A, 2018, 122, 14, 3594], unveiling a correlation between vibrational fingerprints and electronic properties. The evaluation of nonadiabatic coupling matrix elements along generalized normal modes has made possible the interpretation on the molecular scale of the activation of nonradiative relaxation pathways towards the ground electronic state. In particular, two low frequency vibrational modes such as the out of plane bending and dimer breathing and the TCNE central CC stretching play a prominent role in relaxation phenomena from the electronic CT state to the ground state one.